Historical X-Ray on Barrier to Girls Right to Education in Northern Nigeria - Iyanda Kamoru Ahmed; Umoize Stanley (International Journal of Education Sciences, 2024)
This paper focuses on exploring the barrier to girls right to education in northern Nigeria. The paper analyzed that girls are discriminated in many aspects of life; it is belief that the girls are second-class citizen or mere infidel. These bring tremendous misrepresentation of girls and women from both family, schools, institution and the society in general. The paper used secondary sources of data and suggested that educational barrier, socio-economic, traditional and socio-cultural barrier are among the problems preventing girl’s education in the northern Nigeria. The paper also compares the educational ratio of northern and southern girls’ in Nigeria. The paper concluded that the dilemma of the girl-child in the north was distorted by lack of effective and efficient education, general female-led training in all aspect of life, poverty and overall discrimination against female citizens and recommended that government and international communities most support the United Nation Convention of the Right of the Child (UNCRC) and the Nigerian Child Right Act (CRA, 2003) guidelines and all the necessary rights, protection and justice for girls to eliminate the menace of patriarchy. And the traditional norms, religious and other annoying beliefs in the northern Nigeria must be dismissed. It also underlined the need to eradicate patriarchy and advance gender equality in northern Nigeria by doing away with customs, religious doctrine, and other forms of discrimination.
Keywords: Discrimination; educational barriers; gender equality; girl child education; right to education; socio-cultural barriers